Biobleaching of sago waste using xylanolytic Aspergillus sp. for potential use in handsheet preparation - Mariam Dayana, binti Mohd Taha (Universiti Malaysia Sarawak (UNIMAS), 2012)
Bio-bleaching of sago 'hampas' is completed with hemicellulolytic enzymes (xylanases) which hydrolyze hemicelluloses (xylan) in pulp. Aspergillus xylanases are usually used in bio-bleaching of pulp. Three different strains locally isolated of Aspergillus sp. is used in this research, namely Aspergillus flavus NSH9, AspergilJlus niger PANl and Aspergillus versicolor FPI3. The general aim of this study was to screen for Aspergillus sp. that produces the most xylanase and less cellulase or xylanase free cellulose of enzyme for potential application in enzymatic biobleaching of sago'hampas' pulp in paper making. In order to achieve this, solid-state fermentation (SSF) of sago waste using selected Aspergillus sp. for xylanase production was performed. The xylanase produced was extracted and assayed to be utilized for bio-bleaching of sago 'hampas' pulp. Enzymatic bio-bleaching on sago 'hampas' was carry out to yield a good quality paper in terms of brightness from enzymatic pre-treated sago 'hampas '. In this study, A. flavus NSH9 showed moderate enzyme activity with average diameter of clearing zone 2.95 cm on MEA medium and 3.1 cm on corn cob agar during plate screening. Subsequently, it showed the highest xylanase producing strain, with least amount of cellulase activity during submerged fermentation (quantitative screening). In SSF, extracellular xylanase activity ofA. flavus NSH9 reached a maximum (0.597 U/ml) after 5 days of incubation which also revealed the most reduced Kappa number than controls (15.094 points).